PLÁN ESTRATÉGICO PARA LA COOPERATIVA DE AHORRO Y CRÉDITO "CATAMAYO" LTDA., PERÍODO 2016 - 2020 - Robalino Dávila, Gabriela Lizbeth (2016)
As the internal and external context expressed their changes, the companies consider necessary to introduce changes that they will ensure the attainment of its objectives, still the most appropriate means to this end, the formulation of a strategic plan, where they are established action plans and projects consistent with reality. It is so on the basis these aspects mentioned above, it is proposed by the present thesis work, whose general objective is the development of a "STRATEGIC PLAN FOR THE CREDIT UNION "CATAMAYO" LTDA, PERIOD 2016 -2020", with the purpose to give an alternative tool to the management of the entity, in order to achieve profitability and competitive efficiency. To achieve compliance with the specific objectives of this thesis work, started with the analysis of the institutional context, knowing well the current situation of the cooperative. It was subsequently carried out the collection of information through surveys and interview applied to partners, managers and staff of the COAC, also employed the PEARLS Monitoring System for the years 2013 -2014; all this with the purpose of obtaining a deep internal diagnostics; knowing in this way the strengths and weaknesses of the COAC. It is also carried out the bibliographic compilation; through books, documents, newsletters of the ECB, and internet pages; that enabled us to obtain information about the scenarios political, economic, legal, social and 6 cultural, to carry out the analysis of the external environment of the institution, thereby achieving the respective opportunities and threats. With the information obtained is then proceeded to produce the matrix MEI and MEE where assesses the internal and external factors , acquiring a weight of 2.10 and 2.16 respectively, showing us that the Catamayo COAC has an internal position very weak, with below average in effort to get strategies that increase their external opportunities to address the threats. It was also developed the matrix MPC, where it is established that the strongest competitor of the COAC is the Cooperative JEP, while in the weakest are CADECAT and faces. Then with the data obtained in the analysis of the current situation and strategic analysis, produced the SWOT matrix and the matrix of SWOT analysis, where we obtained strategies; then to define the strategic profile of the cooperative, is developing the matrix SPACE, showing the presence of an excellent position to use their strengths with the purpose of: take advantage of the opportunities , overcome weaknesses and to avoid threats for which must be delimited strategies: penetration and market development, product development, integration and diversification. For the proper selection of strategies that must be developed, employed the MPEC array, where sample prioritized strategies, obtaining as the most important to seven. Was later developed the proposal, which restructured the mission and vision of the COAC, with the help of a workshop; they also 7 defined specific values and indispensable then detailed strategic objectives, in relation to these identified the Operational Plans, which has as purpose strengthen the fortresses, eliminating the weaknesses and take advantage of the opportunities and minimize the effects of the threats, to do this is left as a proposal the following projects: Advertising Plan, competitive interest rates and profitable, regulation of credit, training plan for the staff and managers of the COAC training and workshop topics in Financial Education and entrepreneurship, the Partners And citizens in general. Finally ends work in conclusion, that the lack of a strategic direction, prevents the "Credit Union Catamayo Ltda." develop economically in the local market; therefore it is recommended to run this proposed Strategic Plan, since it is directed to the creation of strategies according to the needs and expectations of the institution and its partners, allowing managers to make timely decisions, provided direction and solid foundations for consolidate its growth in the financial market, leveraging its resources efficiently to achieve the project objectives, with a adequate administrative management.